A general and simple method for evaluating the performance of the modified steam Rankine cycle: Thermal cycle splitting analytical method. (15th April 2020) - Xin, Tuantuan; Xu, Cheng; Yang, Yongping
Highlights: A thermodynamic analytical method is proposed for the modified steam Rankine cycle. The modified steam Rankine cycle is split into several simple power cycles. The split power cycles can directly reflect the effectiveness of the modification. The proposed method can also be applied to the modification of the overall system. Abstract: Steam Rankine cycle is the most widely used power cycle for the electric power generation and its process modification can effectively improve the power generation efficiency. To evaluate the thermal performance of these process modifications, the "thermal cycle splitting analytical method" was proposed and illustrated by general formulas. In this analytical method, the modifications of the thermal power cycle are classified into two types, i.e., "power boosting" and "heat saving"; then, the modified cycle is split into a basic cycle and one/several equivalent power cycle(s) (EPC) with simpler thermodynamic process; finally, the effect of the modification can be reflected by the split EPCs, which will not need the overall system simulation. Based on the proposed analytical method, the high-temperature EPCs and low-pressure EPCs were split from the reheat and regenerative cycles, respectively, and the corresponding models for evaluating the efficiency of the modified cycle were developed. Then, the proposed analytical method was utilized to investigate several representative modifications of a typical 1000 MW-stage supercritical power plant, including the cycle itself modification (double reheat, multi-stage regeneration, outer steam cooler, regenerative turbine) and the external heat integration (boiler cold-end energy integration, coal pre-drying and solar-aid power generation), and the obtained results showed a high accuracy through comparing with the overall system simulation. The proposed analytical method might provide a new perspective to analyze the energy saving mechanism of the complex thermal power cycles in a clearer and simpler way.